Theoretical and practical aspects of pedagogy and psychology - Isakova N. V., Filippchenkova S. I., Danilchenko S. L., Pilipchevskaia N. V., Zyrianova E. V., Kaparova K. M., Kostenko E. G., Pozdnyakov A. N., Batyrova E. B., Rushina M. A., Mileiko N. S., Rakhmanova M. N., Zinin S. V., Kazannikova A. V., Kochetova L. F., Miroshnichenko M. V., Blinkov S. N., Kosikhin V. P., Sokunova S. F. (Theoretical and practical aspects of pedagogy and psychology, 2025)
the chapter defines and analyzes the prerequisites for functional literacy of senior preschoolers as the basis for the child's practical activity in the suggested pedagogical conditions. The authors propose an algorithm for organizing educational activities as a condition for developing the level of prerequisites for individual components of functional literacy within the framework of joint activities of the teacher and the child.
Keywords: старший дошкольник; senior preschooler; уровень предпосылок функциональной грамотности; алгоритм организации совместной деятельности; level of prerequisites for functional literacy; algorithm for organizing joint activities